2018
DOI: 10.1016/j.watres.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Reactor staging influences microbial community composition and diversity of denitrifying MBBRs- Implications on pharmaceutical removal

Abstract: The subdivision of biofilm reactor in two or more stages (i.e., reactor staging) represents an option for process optimisation of biological treatment. In our previous work, we showed that the gradient of influent organic substrate availability (induced by the staging) can influence the microbial activity (i.e., denitrification and pharmaceutical biotransformation kinetics) of a denitrifying three-stage Moving Bed Biofilm Reactor (MBBR) system. However, it is unclear whether staging and thus the long-term expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…This is an evidence of how hybrid systems considering different redox environments can improve the possibilities of biological reactors to enhance the biotransformation of many of the compounds present in the complex mixtures of OMPs detected in sewage [10,36,38]. In fact, although higher removal of OMPs is usually reported under aerobic than anoxic conditions, Torresi et al, [39] showed that in absence of a cometabolic limitation, the biotransformation of several OMPs can be more advantageous under anoxic than aerobic conditions.…”
Section: Omp Removalmentioning
confidence: 98%
“…This is an evidence of how hybrid systems considering different redox environments can improve the possibilities of biological reactors to enhance the biotransformation of many of the compounds present in the complex mixtures of OMPs detected in sewage [10,36,38]. In fact, although higher removal of OMPs is usually reported under aerobic than anoxic conditions, Torresi et al, [39] showed that in absence of a cometabolic limitation, the biotransformation of several OMPs can be more advantageous under anoxic than aerobic conditions.…”
Section: Omp Removalmentioning
confidence: 98%
“…The unclassified Sphingobacteriales was found to be prevalent at short HRT and medium SRT. Sphingobacteriales ‐related OTUs have been reported as dominant phylotypes in MBBR and MBR systems and have been linked to degradation of recalcitrant organic compounds . Also, Otu0014, affiliated as Acinetobacter , was dominant at high HRT and medium SRT.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, sulfite reductase was reported to catalyze the cleavage of isoxazole and piperazinyl rings (Jia et al . 2019), and nitrite reductase was correlated with the biotransformation rate constant of some compounds like sulfamethoxazole, erythromycin and trimethoprim (Torresi et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dissimilatory sulfite reductase (EC 1.8.99.3) and nitrite reductase (EC 1.7.2.1) were found to be correlated to the biotransformation of carboxy acyclovir, clarithromycin, furosemide and mecoprop in our study. In previous researches, sulfite reductase was reported to catalyze the cleavage of biotransformation rate constant of some compounds like sulfamethoxazole, erythromycin and trimethoprim (Torresi et al 2018). However, more studies are needed to further support this association and to investigate whether this can be explained by any causal relationship.…”
Section: Enzymatic Correlations With Biotransformation Ratesmentioning
confidence: 98%